Semantic mapping, ontologies and XML standards the key to managing complexity in application integration projects. - Linthicum, David S. (SOA webservices journal.)
When dealing with application integration, as you know by now, we are dealing with much complexity. The notion of ontologies helps the application integration architect prepare generalizations that make the problem domain more understandable. In contrast to abstraction, generalization ignores many of the details and ends up with general ideas. Therefore, when generalizing, we start with a collection of types and analyze commonalities to generalize them.